DISIPLIN WARGA BELAJAR PROGRAM KESETARAAN PAKET C DI PKBM PRIMATRAIN PEKANBARU - Sri Wahyuni; Daeng Ayub Natuna; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research it is based on discipline residents learn program equality package C seen from a series of behavior that show values obedience, allegiance, and order. Formulation problems in this research namely how high discipline residents learn program equality package C in PKBM Primatrain Pekanbaru?, how high obedience people learn the package C equality in pkbm primatrain pekanbaru?, how well the loyalty that citizens learn the package C equality in pkbm primatrain pekanbaru?, how well the program order learning equality package C in pkbm primatrain pekanbaru?, how well the willingness of people learn observe rules in pkbm primatrain pekanbaru?. Research objectives in this research order to know the level discipline residents learn program kesetaraan paket c at pkbm primatrain pekanbaru , and obedience , allegiance , order , and willingness residents learn program equality package C. The population in this research as many as 40 residents learn. Then the researcher determine sample as many as 40 residents learn to research and 20 people we will try to somewhere else with using a technique sampling jenuh. An instrument data collection that is chief with 76 a statement and if the trial live 75 a statement valid for in made instrument research. Through data analysis of the quantitative descriptive analysis. So that discipline residents learn program kesetaraan paket c at pkbm primatrain pekanbaru high. This can be seen from four indicators on discipline residents learning program kesetaraan paket c in pekanbaru pkbm primatrain is considered to be higher, the most high is the presence of obeying the rules.Key words: Discipline, Discipline residents learning